PENGARUH KUALITAS PELAYANAN, PROMOSI DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (PENELITIAN PADA “MEKAR” SWALAYAN-KOPERASI KARYAWAN “MEKAR” PT. GUDANG GARAM TBK KEDIRI) - Khusnul Chotimah; Sri Wahyuni Mega Hastuti; Sumarji Sumarji (Commodities, Journal of Economic and Business, 2021)
Employee cooperatives are cooperatives located in a company and members of the cooperative are employees of the company. the cooperative is given the opportunity to set up its own business unit. Over time the business unit continued to grow rapidly and the business unit changed its name to "MEKAR" Self-Employee Cooperative "MEKAR" Employee PT Gudang Garam Tbk Kediri. The purpose of this study is 1) Test the significance of the effect of service quality on purchasing decisions at the "MEKAR" Supermarkets. 2) Test the significance of the promotion effect on purchasing decisions at the "MEKAR" Supermarket. 3) Test the significance of the effect of product completeness on purchasing decisions at the "MEKAR" Supermarket. 4) Test the significance of the simultaneous influence of service quality, promotion, and product completeness on purchasing decisions at the "MEKAR" Supermarket. This type of research uses quantitative methods with multiple linear regression analysis. This research was conducted at the "MEKAR" Self-Service Cooperative "MEKAR" Employees of Gudang Garam Company Kediri with a sample of 100 members of the "MEKAR" Employee Cooperative of Gudang Garam Company Kediri. The results of this study are 1) The quality of service has a positive and significant effect on purchasing decisions. 2) Promotion has a positive and significant effect on purchasing decisions. 3) Product completeness has a positive and significant effect on purchasing decisions. 4) Quality of service, promotion and completeness of the product together have a positive and significant impact on purchasing decisions.